Method for Printing Functional Protein Microarrays - James B. Delehanty; Frances S. Ligler (BioTechniques)
Piezoelectric dispensing of proteins from borosilicate glass capillaries is a popular method of protein biochip fabrication that offers the advantages of sample recovery and noncontact with the printing substrate. However, little regard has been given to the quantitative aspects of dispensing minute volumes (1 nL or less) at the low protein concentrations (20 μg/mL or less) typically used in microprinting. Specifically, loss of protein sample due to nonspecific adsorption to the glass surface of the dispensing capillaries can limit the amount of protein delivered to the substrate. We demonstrate the benefits of a low ionic strength buffer containing the carrier protein BSA that effectively minimizes the ionic strength-dependent phenomenon of nonspecific protein adsorption to borosilicate glass. Over the concentration range of 20–2.5 μg/mL, the dispensing of a reference IgG in 10 mM PBS including 0.1% BSA resulted in the deposition of 3.6- to 44-fold more IgG compared to the deposition of IgG in standard 150 mM PBS in the absence of BSA. Furthermore, when the IgG was dispensed with carrier protein, the resulting spots exhibited a more uniform morphology. In a direct immunoassay for cholera toxin, capture antibody spots dispensed in 10 mM PBS containing 0.1% BSA produced fluorescent signals that were 2.8- to 4.3-fold more intense than antibody spots that were dispensed in 150 mM PBS without BSA. Interestingly, no differences were observed in the specific activities of the capture antibodies as a result of printing in the different buffers. The implications of these results on the future development of protein biochips are discussed.